The intention to adopt electronic publishing: a case of Malaysian publishers / Zahril Shahida Ahmad - Ahmad, Zahril Shahida (2011)
In the modern era of ICT revolution, the application of electronics to every aspect of human life has become significant. Electronic publishing has emerged as a major development in the media landscape and the adoption of this new media has become an important area of research. The continuance of electronic publishing depends on the adoption of this media by publishers and users. However, a research demonstrates that the rate of adoption of electronic publishing amongst Malaysian publishers is low. In addition, an audit report from 2011 journal in Malaysia revealed that 62.9% of Malaysian journals are still produced only in print format, while only 31.3 % are produced hybrid format (both print and electronic online), only 5.8 are born digitally exclusively on the Internet. It seems that electronic publishing has not penetrated successfully in Malaysian markets.